Whole exome sequencing identified a novel myopalladin gene mutation in a cardiomyopathy patient - Chi Bao, Bui; Minh Hiep, Nguyen; Manh Cong, Nguyen; Thi Thu Trang, Pham; Thi Tham, Luong; Thanh Nga, Ha Thi; Bao Quoc, Vu; Thuat Khoa, Pham Ho; Huynh Nga, Nguyen Thi (Vietnam Journal of Biotechnology, 2020)
Cardiomyopathies (CMs) are a heterogenous group of disorders that affects the heart muscle. In cardiomyopathies, phenotypic overlapping among the inherited cardiovascular diseases (CVDs) limits the ability to establish a diagnosis based solely on clinical features. Here, we developed a next generation sequencing (NGS) assay to analyze a panel of 142 known cardiomyopathy genes in 9 Vietnamese patients from Children Hospital 2, Hochiminh City and Medical University Hospital, Hochiminh City, Vietnam. Whole exome sequencing (WES) - a technique which determines the variations of all coding regions (exons) of the known genes - validated a total of 65 rare variants in 18 cardiomyopathy genes among the studied Vietnamese unrelated patients. Of 65 variants identified, 28 variants were homozygous and the other 37 ones were heterozygous. Among the 65 variants, TTN gene variants accounted the most for 13 mutations, which are known to be benign. Other groups of 9 and 8 mutations belong to SYNE1 and MYPN genes, respectively. Ten out of 65 mutations distributed equally to NDUFV2 and SCN5A gene variants. We detected 6 and 4 variants for SYNE2 and COX15 genes, respectively. Each gene of DMD, KCNE1, NEBL and RBM20 has 2 variants. A single variant was detected for AKAP9, CAV3, DSC2, DSG2, DSP, MYBPC3 and MYH6 genes. Especially, among them, we found a novel heterozygous nonsynonymous mutation c.1527C>G on the MYPN gene. These genetic results support the “pan-cardiomyopathy panel” approach, by which the molecular diagnosis of cardiomyopathies, early identification of arrhythmia development and better clinical management of cardiomyopathic patients are applied.